Seeing invisible support: Understanding provider motivation, intent, and enactment of support. Issue 3 (5th August 2022) - Mason, Adam J.; Shebib, Samantha J.; Boumis, Josephine K.; Allard, Amanda; Holmstrom, Amanda J.; Mazur, Allison
Abstract: The concept of invisible support (Bolger et al.,  2000) has sparked interest among social support researchers. Theoretically, invisible support avoids negative support outcomes related to face threats and, therefore, should lead to better outcomes than traditional support. Unfortunately, empirical tests of invisible support have yielded inconsistent results, potentially due to a lack of conceptual and operational clarity in defining invisible support. The present study addresses this issue, advocating for the inclusion of provider intention to reduce support visibility in the definition of invisible support and establishing the foundation for a typology of invisible support by eliciting participants' experiences with its provision.